(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Student-centered learning is considered one of the most effective approaches in modern education because it focuses on active student involvement in the learning process. This article examines the role of student-centered learning in improving educational quality in higher education institutions. The study is based on the analysis of theoretical sources and practical teaching experiences related to student-centered methods. Qualitative research methods, including observation and comparative analysis, were used to evaluate the effectiveness of this approach. The findings indicate that student-centered learning increases students’ motivation, engagement, and independent thinking skills. In addition, it supports the development of critical thinking and problem-solving abilities, which are essential for academic success. The article concludes that the implementation of student-centered learning strategies can significantly enhance educational quality and contribute to better learning outcomes in higher education.